2016
DOI: 10.1038/srep20219
|View full text |Cite
|
Sign up to set email alerts
|

A metasurface carpet cloak for electromagnetic, acoustic and water waves

Abstract: We propose a single low-profile skin metasurface carpet cloak to hide objects with arbitrary shape and size under three different waves, i.e., electromagnetic (EM) waves, acoustic waves and water waves. We first present a metasurface which can control the local reflection phase of these three waves. By taking advantage of this metasurface, we then design a metasurface carpet cloak which provides an additional phase to compensate the phase distortion introduced by a bump, thus restoring the reflection waves as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
101
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 184 publications
(106 citation statements)
references
References 34 publications
0
101
0
Order By: Relevance
“…Yang et al 25 have demonstrated that a metasurface carpet cloak constructed by AMS can be used to hide large objects. In this section, we demonstrate that acoustic carpet cloak can also be designed by our AMS.…”
Section: Acoustic Carpet Cloak Designed By Amsmentioning
confidence: 99%
“…Yang et al 25 have demonstrated that a metasurface carpet cloak constructed by AMS can be used to hide large objects. In this section, we demonstrate that acoustic carpet cloak can also be designed by our AMS.…”
Section: Acoustic Carpet Cloak Designed By Amsmentioning
confidence: 99%
“…Since it is first proposed, TO has found wide applications in designing novel electromagnetic (EM) devices, including invisibility cloak16171819, hyper-lens2021, waveguide222324, superscatters252627, etc. In this peper, we theoretically design a novel lens, which can not only take panoramic photos, but also compress the image, for it can fit the visual angle of the average person.…”
mentioning
confidence: 99%
“…The acoustic analogue to electromagnetic metamaterials has already been validated in earlier works, and the possibility of extending the metamaterials concept to acoustic waves has already been investigated1. Building on this work, acoustic metamaterials have focused on developing artificial structures that can manipulate and control sound waves in unconventional ways2, made possible by the creation of unusual material properties such as double negativity (negative mass density and modulus)34, zero – or even negative – refractive index5678, acoustic imaging910, cloaking111213, transformation acoustics14, active acoustic metamaterials15, and acoustic metasurfaces1617. As a fundamental research subject in acoustic metamaterials, element design has been focused primarily on two kinds of strategies – locally-resonant materials318 and effective medium theory based composites19.…”
mentioning
confidence: 99%